Preparing Education Students for an International Future? Connecting Students’ Experience to Institutional Contexts - Alexiadou Nafsika; Kefala Zoi; Rönnberg Linda (Sage Publications, 2022)
This article focuses on “internationalization at home” (IaH) for education students in Swedish Universities and its significance for their professional formation and future practice. We draw on research in two large institutions and explore the perceptions and experiences of internationalization of home students in education. We find that while the “intercultural” understanding of students is well developed, the international and intercultural dimensions of experiencing IaH are limited, due to several institutional and learning environment contexts. This has consequences for the social dimensions of future teaching practice. In addition, the perception of the discipline as “national” is significant in shaping the outlook of students toward international questions and their own future personal and professional mobility. We contextualize these findings using documentary analysis and staff interviews, and argue that to achieve intercultural and international learning environments of quality, social relevance, and long-term social benefit, we need to rethink how internationalization perspectives are integrated in teacher education courses.